Training on the Use of GNS3 in Computer Networks Learning for Vocational High School Teachers - Amrizal; Khomarudin, Agus Nur; Jamaluddin; Jingga, Trinovita Zuhara; Hendra; Nurtam, M Riza; Laksmana, Indra; Syukriadi; Aulia, Romy; Novita, Rina; Nazli, Rabby; Putri, Ega Evinda; Febrina, Widya (Indonesian Journal of Community Services Cel, 2022)
The development of Science and Technology (IPTEK), especially information technology, has had a positive impact on all aspects of human life, including education aspect. The teaching and learning process is the core of the whole educational process. The quality of teaching and learning is determined by the teacher and the students themselves as subjects or actors in the process. Therefore, a teacher is required to always improve skills through learning activities/seminars/training related to their competence field. This Community Service Program (CSP) used mentoring methods in its implementation, while the approaches used were classical and individual approach. This CSP activity has succeeded in providing debriefing and training for teachers to install computer networks using the GNS3 software. The training participants in this CSP were teachers of SMKN 1 Suliki, Lima Puluh Kota Regency and SMKN 1 Ampek Angkek, Agam Regency, West Sumatra. To find out the effectiveness of this CSP activity, a questionnaire was used as an assessment instrument. Based on the tabulation results, it was found that this CSP activity obtained an average value of 82.71% in the good category. Even though this activity has obtained good results from CSP participants, consistent efforts are needed to increase the effectiveness of CSP implementation for the next period. Efforts to increase the effectiveness of CSP implementation are also based on several suggestions and input submitted by CSP participants through an effectiveness questionnaire. The suggestions and input submitted by several participants became evaluation material for the CSP implementation team of the Computer Engineering Study Program, Payakumbuh State Agricultural Polytechnic in the future.